(3GdcJH GdJj de jPcQgG LGdjfhS aj agQSJ cJHgs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s ((3eMehO UObi s)
(3ChdgG (B:s
(3GeG Ef LGdjfhS bO hVY cJHkG ZjQ GdcJH GdJi PcQgG ai agQSJg, abO jOd Ydi Pdc eG hLO ef gPg GdcJH, aEfgG JOd Ydi ePgH cdGeg heYGfjg OdGdI HjfI Ydi faSg s
(3BNQgG (B:s
(3bO PcQ ai cJHg eeG de jKHJg ai GdagQSJ hdGhbYJ EdjfG fSNI , hai GdCNdGW Ydi QCi aOcSGZhQK ebGdI , hebGdI ajef jMJGL ai GdQHjY Edi GdaUO s
(3fbdgG GdfGSN Yf fSNI eZQHjI GdCUd HQbe (B3590 (3BjGUhajGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B206 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3agGQS JjehQ (B138) s
Keywords: (3GdWHs